Mutational analysis of positively charged residues in the N‐terminal region of the class IIa bacteriocin pediocin PA‐1. (19th December 2013) - Song, D.F.; Li, X.; Zhang, Y.H.; Zhu, M.Y.; Gu, Q.
Abstract The significance of positively charged residues for the target cell binding of pediocin PA‐1 bacteriocins was studied by site‐directed mutagenesis. Most of the charged residues are located in the N‐terminal half of the peptide, which is thought to mediate the initial binding of these bacteriocins to their target cells through electrostatic interactions. Mutated peptides in which the positively charged residues were substituted or increased in number were constructed, and some of these peptides exhibited a twofold increase in the bacteriostatic activity. The greatest enhancement was achieved by introduced the positive charges at position 13, their results show the benefits of introducing an additional cationic residue within this patch in the middle of the N‐terminal half of pediocin PA‐1 bacteriocins. Thus, the presence of additional cationic residues in the N‐terminal half influenced the electrostatic binding of this bacteriocin to its target cells and increased the potency of the peptide on the potency of Micrococcus luteus and Staphylococcus aureus. Significance and Impact of the Study No previous work has systematically examined the N‐terminal cationic residues of the pediocin PA‐1 for their functional importance or redundancy. In this study, we examined the structure–function relationships of pediocin PA‐1 by site‐directed mutagenesis. Mutated peptides in which the positively charged residues were substituted and increased in number exhibited a twofold increase in the bacteriostatic activity. This study demonstrated the importance of the cationic patch in the N‐terminal half of pediocin PA‐1. The cationic residues influenced the electrostatic binding of the bacteriocin to the target cells and had a greater effect on the potency of the peptide towards Micrococcus luteus and Staphylococcus aureus.